2007
DOI: 10.1007/s11136-007-9188-2
|View full text |Cite
|
Sign up to set email alerts
|

Field testing of a European quality of life instrument for children and adolescents with chronic conditions: the 37-item DISABKIDS Chronic Generic Module

Abstract: Reliability, construct validity as well as convergent and discriminant validity of the DCGM-37 were shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
142
0
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 130 publications
(159 citation statements)
references
References 42 publications
6
142
0
9
Order By: Relevance
“…different countries participating at the same time in the construction of a new instrument) (Simeoni et al, 2007), and revealed sound psychometric properties (Petersen, Schmidt, Power, Bullinger, & The Disabkids Group, 2005;Simeoni et al, 2007;. The instrument clearly accomplished all the requirements to paediatric QL measures proposed by the WHO (1993), and complied with most suggested criteria to assess instrument developmental adequacy (Bruil & Detmar, 2005;Bullinger & Ravens-Sieberer, 1995;Wallander, Schmitt, & Koot, 2001).…”
Section: The Contribution Of Disabkids Projectmentioning
confidence: 83%
See 1 more Smart Citation
“…different countries participating at the same time in the construction of a new instrument) (Simeoni et al, 2007), and revealed sound psychometric properties (Petersen, Schmidt, Power, Bullinger, & The Disabkids Group, 2005;Simeoni et al, 2007;. The instrument clearly accomplished all the requirements to paediatric QL measures proposed by the WHO (1993), and complied with most suggested criteria to assess instrument developmental adequacy (Bruil & Detmar, 2005;Bullinger & Ravens-Sieberer, 1995;Wallander, Schmitt, & Koot, 2001).…”
Section: The Contribution Of Disabkids Projectmentioning
confidence: 83%
“…The diagnoses of asthma and epilepsy were chosen as inclusion criteria, in agreement with the previous work of semantic validation and pilot study of the Portuguese versions of DISABKIDS-37 (Carona, Bullinger, & Canavarro, 2011). Besides, asthma was required as the common condition to be tested across all countries participating in the original DISABKIDS project (Simeoni et al, 2007) and subsequent instrument cross-cultural adaptations.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Generic instruments include the KIDSCREEN index. This index assesses QoL in children 8 years and older based on ten questions derived from a large representative health survey conducted in different European countries [6]. The DISABKIDS index consists of a generic core instrument as well as several condition-specific modules that provide insight into the QoL of children and adolescents with chronic conditions, and it includes parental perspectives [7].…”
Section: Understanding Psychological Statusmentioning
confidence: 99%
“…The 'DISABKIDS Chronic Generic Module' (DCGM-37; The DISABKIDS Group Europe, 2006;Petersen et al, 2005;Simeoni et al, 2007; is an age group-adapted, condition-generic, as well as multidimensional measurement, assessing general subjective CGQOL of children and adolescents (8 to 16 years old) with chronic conditions (e.g., asthma, arthritis, diabetes etc.). This module is a questionnaire comprising of 37 items, belonging to six facets (six items each, with the exception of the 'emotions' facet, which includes seven items) and one summary score.…”
Section: Original Measure (Dcgm-37)mentioning
confidence: 99%